Occupational and environmental lead exposure to adolescent workers in battery recycling workshops. (December 2015) - Kazi, Tasneem Gul; Shah, Faheem; Afridi, Hassan Imran; Naeemullah,
Lead (Pb), as other environmental neurotoxicant substances, has the capability to interfere with many biochemical events present in cells throughout the body. In the present study, the environmental and occupational exposure to Pb has been assessed by analyzing the scalp hair samples of male adolescents aged 12–15 years, who have worked for the last 12–36 months in Pb battery recycling workshops (BRWs). For comparative purposes, gender and age-matched subjects living in the vicinity of recycling workshops as well as in areas without industrial activity were used as controls. The scalp hair samples were oxidized by acid in a microwave oven prior to determination of Pb by electrothermal atomic absorption spectrometry. The results indicated that both workers and nonworking exposed subjects had higher levels of Pb than nonexposed controls. The contents of Pb in scalp hair of adolescent workers in the present study were compared with those reported in other studies.